The Effectiveness of E-Modules Through Physics Modeling Learning to Improve Problem Solving Skills - Arifuddin, Muhammad; Syifa, Linda Nur; Mahardika, Andi Ichsan; Mastuang, Mastuang (Kasuari: Physics Education Journal (KPEJ), 2023)
The use of conventional teaching materials with less innovative learning models results in a lack of problem solving skills possessed by students. This study aims to produce teaching materials in the form of vibration material e-modules through effective and feasible physics modeling learning to improve students' problem solving skills using the ADDIE development model. The subjects of the research were 34 class XI C students of SMAN 5 Banjarmasin. Data collection techniques using learning outcomes tests through pre-test and post-test. The results showed that the electronic module was stated to be very effective in terms of the average n-gain score for measuring problem solving skills of 0.78 in the high category. As well as there was a significant increase between before and after using the e-module through the paired sample t-test. Thus, the vibration material e-module through physics modeling learning is declared effective and significant in improving students' problem solving skills